A simplified approach for producing Tier 2 enteric-methane emission factors based on East African smallholder farm data - Ndung'u, Phyllis W.; Toit, C.J.L. du; Takahashi, T.; Robertson-Dean, M.; Butterbach-Bahl, Klaus; Merbold, Lutz; Goopy, John P. (Commonwealth Scientific and Industrial Research Organisation, 2023)
Context. Accurate reporting of livestock greenhouse gas (GHG) emissions is important in developing effective mitigation strategies, but the cost and labour requirements associated with on-farm data collection often prevent this effort in low- and middle-income countries.